The aesthetic experience of the sublime for a group of Highly Sensitive Persons: Maselli's figurative style vs. Rothko's abstract expressionism - Echarri, Fernando; Miguéliz, Ignacio; Verea, Natalia; Barrio, Teresa (Frontiers in Psychology, 2025)
Contemporary art museums have become important learning environments to promote visitor aesthetic education. Each piece of art constantly sends different messages to the viewer and creates a person-art connection that can provide significant experiences. These connections can be established in the contemplation of the sublime. In order to understand how these connections occur, researchers present a study about the relationship between aesthetic experience and the sublime that can happen through the contemplation of contemporary art, both figurative and abstract. Specifically, this aesthetic experience with the sublime has been studied in a group of highly sensitive individuals. The abstract work of Mark Rothko's masterpiece “Untitled” (1969) and the figurative work of Fernando Maselli “Artificial Infinite” (2014) have been utilized. The study includes an instrument for the evaluation of the “aesthetic experience of the Sublime,” in which four dimensions—perception, emotion, cognition, and spiritual—are considered. This instrument has been applied to a group of highly sensitive people. Based on mixed quantitative and qualitative data analysis, results show that these individuals can experience contemporary art painting intensely by perceiving changes in its sensitive features while vanishing self-references of time and space.